Altruism as Perspective of Medical Students - Wiwik Kusumawati; Yunita D Indriani (Universitas Muhammadiyah Yogyakarta, 2019)
Altruism is an important attribute for medical doctors and other health professionals. The behavior of altruism must be understood and trained in the early stage of medical education. The aim of this study was to know the medical students’ perception of altruism. This was a qualitative study and the participants were 24 medical students who were chosen by purposive sampling with criterion reference. The data were collected using in-depth interviews and focus group discussions. The data then were transcribed into verbatim and analyzed using the constant comparative method. This study revealed 90 codes, 16 themes, and five final themes. The final theme consisted of 1) altruism and attribute of medical professions, 2) altruism and influential factors, 3) altruism of medical students, 4) medical profession from a student perspective, and 5) altruism and malpractice. Altruism and medical professionalism are important attributes of the medical profession. There are many factors that can influence medical student's altruism, it can be internal or external factors. Medical students have various levels of altruism and we can assess the degree of altruism of medical students through their understanding of the medical profession. A low degree of altruism of doctor may cause unexpected things such as malpractice.